A Review Paper on Internet of Nano Things - Patil, Vishal S; Chauhan, Gauri J; Morey, Aparna P; Bhute, Suraj S; Borkar, Tejaswini S (International Journal of Computer Sciences and Engineering, 2019)
The Internet of Nano Things taking IoT to next level. Nanotechnology is science technology in which size of devices are much smaller which contributed greatly in computing and electronics, leading to faster ,smaller and more profitable system that can be use for communication and storing of large data. It is also use of creating devices, machines in nano size by integrating molecules or atoms. Nanotechnology is a building block of Internet of Nano Things(IoNT) which include basic unit called as Nano machines which perform simple task like sensing and actuating. The interconnection of nano devices with existing internet called as “Internet of Nano Things”. Nanotechnology has provide new solution to benefit society in different sector like information technology, medicines, transportation, military field , as well as industrial purpose. In this paper we are showing the architecture of Nano machines, network architecture ,application field, challenges in Internet of Nano Things (IoNT) and help to researchers to find solution for challenges and increase the use of Internet of nano Things (IoNT) in future in different field.